FACTORS ASSOCIATED WITH THE USE OF HEALTH WEBSITES AND APPS AMONG STUDENTS IN MEDICINE AND SPORTS: Upotreba sajtova i aplikacija o zdravlju - Gazibara, Tatjana; Cakic, Milica; Cakic, Jelena; Zejnelagic, Redzeb; Popovic, Aleksandra; Grgurevic, Anita (Medical Research, 2024)
Introduction/Aim: The global digital network allows fast exchange of information. Students of sports and medicine will be the future promoters of healthy behaviors. The aim of this study was to examine the use of health-related websites and apps among students of sports and medicine in their final undergraduate study year. Method: This cross-sectional study was conducted at the Faculty of Sports and Physical Education and the Faculty of Medicine, University of Belgrade, Serbia, in the period April-October 2017. A total of 390 students (89 in sports and 301 in medicine) were recruited. Data were collected using an anonymous questionnaire. Results: Students did not differ in terms of frequency of use of health-related websites (79.8% sport vs. 77.7% medicine; χ2=0.167, p=0.771) and apps (39.3% sport vs. 49.2% medicine; χ2=2.672, p=0.116). Fitness and diet were the most common topics that all students sought. The stronger influence of online health information on students’ health-related decision-making was associated with the use of health-related websites in both groups of students. Additionally, medical students who used the Internet more often were also more likely to read health-related websites. In terms of apps, being female and using the Internet from a younger age was associated with the use of health apps among sports and medical students, respectively. Conclusion: Many students in sports and medicine read health websites, but fewer students use health apps. Students’ interest in health topics online is similar to other student populations. Websites and apps could be an avenue for the promotion of healthy behaviors.